The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.4314/evj.v23i1.5
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence, risk factors and antimicrobial susceptibility profile of <i>Salmonella</i> isolated from dogs of Ambo, Bako and Gojo towns of West Shoa, Ethiopia

Abstract: Salmonella is the most known zoonotic bacterial agent, which produces salmonellosis in animals as wells as in humans. The objectives of this study were to estimate the prevalence, to determine antimicrobial susceptibility and to assess risk factors associated with Salmonella shedding in dogs in selected towns of West Shoa Zone, Oromia, Ethiopia. Using a cross-sectional design, a total of 438 rectal swab samples were collected from randomly selected dogs for isolation and identification of Salmonella using stan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
3
1

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 14 publications
1
3
1
Order By: Relevance
“…Furthermore, Sultan et al [ 38 ] and Kiflu et al [ 15 ] reported insignificant difference in the prevalence of Salmonella between age groups examined. In contrary to our finding, Núñez-Castro et al [ 61 ] from Mexico reported that dogs under 1 year are more likely to acquire Salmonella than dogs older than 1 year, while Zewdu et al [ 39 ] from Ethiopia reported that older dogs harbor more Salmonella than younger dogs. Often it is difficult to compare different findings, because different age profiles are seen in different studies and it is confounded by differences in sampled population lifestyles and owners dog caring practices.…”
Section: Discussioncontrasting
confidence: 99%
See 4 more Smart Citations
“…Furthermore, Sultan et al [ 38 ] and Kiflu et al [ 15 ] reported insignificant difference in the prevalence of Salmonella between age groups examined. In contrary to our finding, Núñez-Castro et al [ 61 ] from Mexico reported that dogs under 1 year are more likely to acquire Salmonella than dogs older than 1 year, while Zewdu et al [ 39 ] from Ethiopia reported that older dogs harbor more Salmonella than younger dogs. Often it is difficult to compare different findings, because different age profiles are seen in different studies and it is confounded by differences in sampled population lifestyles and owners dog caring practices.…”
Section: Discussioncontrasting
confidence: 99%
“…In our findings, there was no significance difference between medium, fat and thin body condition score of the dogs, which is in accordance with the reports of Kiflu et al [ 15 ], Sultan et al [ 38 ], and Zewdu et al [ 39 ], in that insignificant difference in the prevalence of Salmonella was recorded between body condition categories of studied dogs. Similarly, our study didn’t show significance difference between age categories of dogs.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations